Study on hysteresis and threaded fitting behavior of bolted joint with non-parallel bearing surface. (1st April 2022) - Tan, Longfei; Wang, Chengyu; Liu, Yang; Sun, Wei; Zhang, Wei
Highlights: An parameter identification analytical model was developed based on the hysteresis characteristic of single bolt lap beam. Bolt friction coefficient test technique was adopted to improve the accuracy of model parameter identification. The stiffness and damping of the joint were quantitatively characterized by this identification method. Improved modeling technique is used to analyze variation characteristics of joint parameters. The threaded interaction mechanism and its influence on the hysteresis characteristics of bolted joint are analyzed. Abstract: Obtaining the static hysteresis behavior of bolted joint and identifying joint parameters are of great significance to design and formulate the assemble process for the bolted joint. In this study, the relationship between the hysteresis behavior and joint parameters of bolted joint is proposed by the bolt analytical model. Then, the tightening process and thread fitting mechanism of bolt under non - parallel bearing faces are analyzed. Next, the effects of non-parallel bearing surface and external load on the joint parameters are analyzed by parametric finite element method. Finally, the friction coefficient extraction and static hysteresis test experiment of the single bolt lap beam are carried out, which verified the theory and finite element model. The results show that establishing a single bolt lap beam with threads and introducing friction coefficient can more accurately predict the stiffness and damping of the bolted joint. The tightening of the non-parallel bearing face bolt generates an additional threaded contact friction pair, which causes a deviation of preload and affects the identification results of the joint parameters.